Front Cover: Thioether‐Containing Copper Complexes as PHM, DβM, and TβM Model Systems (Eur. J. Inorg. Chem. 1/2022). Issue 1 (15th December 2021) - Gómez‐Vidales, Virginia; Castillo, Ivan
Abstract : The Front Cover shows the synergic action of copper and sulfur in thioether‐containing copper monooxygenases that generate mammalian and invertebrate neurotransmitters. The review reports efforts of synthetic chemists to mimic the active sites of peptidylglycine α‐hydroxylating monooxygenase, dopamine β‐monooxygenase, and tyramine β‐monooxygenase. N ‐ and S ‐donors, the latter as thioethers, reproduce the properties of the monocopper sites that hydroxylate substrates to produce neurotransmitters. Redox properties are modulated by the thioethers to generate cupric‐superoxo intermediates, perhaps acting as hemilabile donors. The cover was designed by Erika Osorio. More information can be found in the Minireview by V. Gómez‐Vidales and I. Castillo .